Open Drug Scenes Survey in Brazilian cities: main findings from São Paulo, Fortaleza, and Brasília - Clarice Sandi Madruga; Kátia Isicawa de Sousa Barreto; Danilo Seabra; André Constantino Miguel; Cláudio Jerônimo da Silva; Gleuda Simone Apolinário; Guilherme Godoy; Lidiane Nogueira Rebouças; Natália Alexandre Ferreira; Quirino Cordeiro; Rogério Adriano Bosso; Ronaldo Ramos Laranjeira (Revista Brasileira de Epidemiologia)
ABSTRACT Objective: The latest edition of the Open Drug Scenes Survey in Brazilian Cities (LECUCA) investigated social vulnerability, health, and the use of the Psychosocial Care Network by attendees of open drug scenes (ODSs) involving crack cocaine in São Paulo, Fortaleza, and Brasília between 2021/2022. Methods: Since 2016, LECUCA has used Time-Location Sampling (TLS) to select probabilistic samples representative of the population of ODS attendees. Results: We interviewed 579 participants in São Paulo, Fortaleza, and Brasília, obtaining a response rate of 75%. We found no difference in ODS attendees regarding the prevalence of sociodemographic indicators and time living in the ODS. The prevalence values of attendees who had never been homeless before living in the ODS and those living in their homes were equally high in the three capitals. Fortaleza stood out for having lower rates of homelessness and limited access to specialized health services, whereas Brasília had high rates of searching for emergency services due to drug use and greater access to all modalities of health and assistance services. Unprotected sex was prevalent over one third of ODSs attendees, and none of the capitals had more than half of the attendees testing for tuberculosis and sexually transmitted infections. Rates of pregnancy complications were high in all three capitals, with São Paulo accounting for the lowest rates. Conclusion: LECUCA provides significant subsidies to governmental and institutional managers, aiming at catalyzing the formulation of public policies and care strategies based on data and evidence.